Microplastic accumulation and reduction in shellfish (Polymesoda bengalensis) using NaCl solution - Deswati Deswati; Emriadi Emriadi; Aura Monica Selfi; Fitri Wiya Elsa; Suparno Suparno; Putra Adewirli (Journal of the Serbian Chemical Society)
This study investigates microplastic (MP) contamination in shellfish (Polymesoda bengalensis) and evaluates the effectiveness of NaCl treatment in reducing MP levels in consumed shellfish. Samples were collected from three estuaries in West Sumatra, Indonesia: Batang Arau, Bungo Pasang and North Punggasan. The samples were analyzed using trinocular microscopy and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) to quantify MP abundance and identify polymer types. MP concentrations ranged between 750–1000 particles/kg in shellfish and 400–500 particles/kg in sediments, with Batang Arau exhibiting the highest levels. The predominant MP forms detected were fragments (82.36 %), films (13.72 %) and fibers (3.92 %), with sizes primarily between 100–300 μm. The primary polymers identified included polyvinyl chloride (PVC), polyamide (PA) and polyethylene terephthalate (PET). A series of treatments using NaCl solutions at varying concentrations (10, 20 and 30 %) and immersion durations (10, 20 and 30 min) demonstrated that a 30 % NaCl solution for 30 min effectively reduced MP levels by 85 %, decreasing MP concentration in shellfish flesh to 150 particles/kg. These findings highlight the potential of NaCl treatment as a cost-effective method for reducing MP contamination in shellfish, contributing to improved seafood safety and providing insights into MP pollution management in aquatic ecosystems.